Isolation and molecular characterization of Bacillus thuringiensis found in soils of the Cerrado region of Brazil, and their toxicity to Aedes aegypti larvae - Lobo, Katiane dos Santos; Soares-da-Silva, Joelma; Silva, Maria Cleoneide da; Tadei, Wanderli Pedro; Polanczyk, Ricardo Antonio [UNESP]; Soares Pinheiro, Valeria Cristina (Soc Brasileira Entomologia, 2018)
This study investigated the potential of Bacillus thuringiensis isolates obtained in the Cerrado region of the Brazilian state of Maranhao for the biological control of Aedes aegypti larvae. The isolates were obtained from soil samples and the identification of the B. thuringiensis colonies was based on morphological characteristics. Bioassays were run to assess the pathogenicity and toxicity of the different strains of the B. thuringiensis against third-instar larvae of A. aegypti. Protein profiles were obtained by sodium dodecyl sulfate polyacrylamide gel electrophoresis. Polymerase chain reaction assays were used to detect the toxin genes found in the bacterial isolates. Overall, 12 (4.0%) of the 300 isolates obtained from 45 soil samples were found to present larvicidal activity, with the BtMA-104, BtMA-401 and BtMA-560 isolates causing 100% of mortality. The BtMA-401 isolate was the most virulent, with the lowest median lethal concentration (LC50) (0.004 x 10(7) spores/mL), followed by the Bacillus thuringiensis var. israelensis standard (0.32 x 10(7) spores/mL). The protein profiles of BtMA-25 and BtMA-401 isolates indicated the presence of molecular mass consistent with the presence of the proteins Cry4Aa, Cryl lAa and Cytl, similar to the profile of Bacillus thuringiensis var. israelensis IPS-82. Surprisingly, however, none of the cry and cyt genes analyzed were amplified in the isolate BtMA-401. The results of the present study revealed the larvicidal potential of B. thuringiensis isolates found in the soils of the Cerrado region from Maranhao, although further research will be necessary to better elucidate and describe other genes associated with the production of insecticidal toxins in these isolates. (C) 2017 Sociedade Brasileira de Entomologia. Published by Elsevier Editora Ltda. This is an open access article under the CC BY-NC-ND license.
Keywords: Biological control; Entomopathogenic bacteria; Vector